Hysteroscopic polypectomy in 240 premenopausal and postmenopausal women - Sangchai Preutthipan (2018)
Objective: To ascertain the therapeutic efficacy and safety of hysteroscopic polypectomy in 240 premenopausal and postmenopausal patients. Design: Retrospective study. Setting: Tertiary university hospital. Patient(s): Two hundred forty patients with intrauterine endometrial polyps, who mostly suffered from abnormal uterine bleeding and infertility. Intervention(s): Hysteroscopic polypectomy using various instruments including microscissors, grasping forceps, or electrosurgery either with a monopolar probe or a resectoscope. Main Outcome Measure(s): Operating time, amount of glycine absorption, complications, resumption of normal menstruation, cumulative pregnancy rate, and recurrent rate of polyps after hysteroscopic surgery. Result(s): Resectoscopic polypectomy needed more operating time, had more glycine absorption and complications, but less recurrence than other hysteroscopic techniques. The resectoscope had a 0% recurrence rate and that grasping forceps had a 15% recurrence rate. A total of 21 (8.7%) complications occurred, but no major complications were noted. After long-term follow-up of 9 years and 2 months, those with abnormal uterine bleeding resumed normal menstruation in 93.1% and those with infertility had a cumulative pregnancy rate of 42.3%. There was no statistical difference in reproductive outcome between patients having polyps ≤ 2.5 cm and >2.5 cm. Conclusion(s): We found hysteroscopic polypectomy to be effective, safe, minimally invasive procedure with low rate and mild complications. Restoration of reproductive ability did not depend on the size of the removed lesion. Resectoscopic surgery is more preferable to prevent recurrence of polyps. © 2005 by American Society for Reproductive Medicine.